2008
DOI: 10.1002/mop.23875
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐wideband bandpass filter using hybrid microstrip‐defected‐ground structure

Abstract: A novel ultra‐wideband (UWB) bandpass filter (BPF) with a fractional bandwidth (FBW) of about 110% is presented using the hybrid microstrip‐defected‐ground structure (DGS). The proposed filter was designed using a combination of hybrid microstrip‐defected‐ground structure lowpass filter (LPF) with typical quarter‐wavelength short‐circuited stubs highpass filter (HPF), followed by an optimization for tuning in‐band performance. The high selectivity LPF using hybrid microstrip and four backside slots on ground p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A novel ultra wideband bandpass filter based on DGS with the fractional bandwidth of 110% is presented in literature [8]. Bandpass filter is designed with the use of low-pass and high pass filter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel ultra wideband bandpass filter based on DGS with the fractional bandwidth of 110% is presented in literature [8]. Bandpass filter is designed with the use of low-pass and high pass filter.…”
Section: Introductionmentioning
confidence: 99%
“…Generally circularly polarized nature can be obtained with single or multiple feeds for a limited band of frequencies. Research reported on CP DRA with simple configuration and less space on feed substrate shows less axial ratio bandwidth [5][6][7][8][9][10][11]. Wide band CP operation therefore requires either dual feed network [12,13] or some special configuration [14-16].…”
Section: Introductionmentioning
confidence: 99%
“…Another type of UWB BPF was developed, based on a stub‐loaded multiple‐mode resonator, so that several resonant modes within the UWB passband could be obtained by placing three open‐ended stubs at appropriate positions and adjusting their lengths . A novel UWB BPF with compact size and improved upper stopband performance was also realized using a multiple‐mode resonator . It was discovered that a stepped‐impedance stub‐loaded resonator provides more freedom with regard to adjusting the resonant frequencies and also enables the creation of two transmission zeros at the lower and upper ends of the passband .…”
Section: Introductionmentioning
confidence: 99%
“…This MMR has compact size and improved upper stopband performance. A novel UWB BPF with compact size and improved upper stopband performance was also realized using a MMR [7,8]. The resonators proposed in [9] offer the advantages of more degrees of freedom for adjusting the resonant frequencies and two transmission zeros at both the lower and upper ends of the passband.…”
Section: Introductionmentioning
confidence: 99%